Verbal Violance: The Phenomenon Among School Age: Fenomena Kekerasan Verbal Terhadap Anak Usia Sekolah - ainil fitri; Pelangi Lestari (LPPM Universitas Abdurrab, 2023)
Background: A time when children are often selfish, show stubbornness, do not want to follow the rules set by parents , rebel which is the case It is done by children to gain freedom and satisfy their curiosity, this period is called the period of school-age children. Conditions like this often make parents feel that their children are difficult to manage so that parents tend to force children to follow what parents want so that they don't Aware of parents committing verbal abuse on their children. Poor mental development, disrupted social relationships with peers and adults, aggressive behavior, often feel lonely , and make children experience Emotional distress is some of the impacts often experienced by children who are victims of verbal abuse. Objective: The purpose of this study is to determine the phenomenon or incidence of verbal abuse in school-age children. Methodology: This study uses a type of quantitative research with a descriptive research design. This research was conducted at SD